Balancing professional tension and deciding upon the status of death: Making end-of-life decisions in intensive care units. Issue 1 (23rd January 2016) - Konstantara, Emmanouela; Vandrevala, Tushna; Cox, Anna; Creagh-Brown, Benedict C; Ogden, Jane
This study investigated how intensivists make decisions regarding withholding and withdrawing treatment for patients at the end of their lives. This involved completing in-depth interviews from two sites of the South of England, United Kingdom by twelve intensivists. The data collected by these intensivists were analysed using thematic analysis. This resulted in the identification of three themes: intensivists' role, treatment effectiveness, and patients' best interest. Transcending these were two overarching themes relating to the balance between quantity and quality of life, and the intensivists' sense of responsibility versus burden. The results are considered in terms of making sense of death and the role of beliefs in the decision-making process.